The Use of Cohesive Devices in Descriptive Text by English Training Participants at PSTâ€ - kifti halimah islami; Mursid Saleh; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2022)
Today, many media to large companies are starting to invest English skills in their employees, including Pura Smart Technology (PST). This research aims to find out the use of cohesive lexical devices, the use of cohesive grammatical devices, the correctness of cohesive device uses, and the correlation of cohesive device use and descriptive text writing skills of the participants. The researcher took eleven employees as the participants. The researcher analyzed the data with Halliday & Hasan's theory, Coh-Metrix 3.0, and Spearman Correlation. The results were repetition with 54.92%, synonym with 6.81%, hyponym with 33.71%, meronym with 3.40%, and collocation with 1.14%. In terms of grammatical cohesion, the researcher found a reference with 29.54% and conjunction with 69.31%. The result also showed that the participants' cohesive device use excellence was 39.65%, with a very strong correlation, (rs) = 0.95. The researchers found that the English training participants had low mastery of cohesive device use quality. The researchers also found that the participants' cohesive devices and writing skills had a strong, significant, and immense correlation. The researchers suggest that future researchers upgrade the study's object and involve participants from different and complex backgrounds. From the pedagogical perspective, cohesive device uses are important to create a good image and judge an excellent educational background between the writer and the reader while understanding the meaning. Thus, writers can produce texts without any hoax information nowadays. Practically, these results help people use text appropriately in formal and non-formal settings.